Ring the Judas bell. - Forman, James D. (New York Bell Books, 1965)
Taken from their homes by guerrillas during the civil war, a group of Greek children try to make their way back from a prison camp in the Yugoslav mountains.
Keywords: Greece -- History -- Juvenile fiction. -- Civil War, 1944-1949.; Greece -- History -- Fiction. -- Civil War, 1944-1949.